Relation between Mental Health Status and Psychosocial Stressors among Pregnant and Puerperium Women in Japan: From the Perspective of Working Status - Fumi Takeda; Nanako Tamiya; Haruko Noguchi; Takafumi Monma (Intelektual Pustaka Media Utama, 2012)
Mental health problems during pregnancy and postpartum periods are one of the alarming health issues among women in Japan. This study analyzed data on the Japanese version of the Kessler 6 (K6), specific psychosocial stressors, and working status of pregnant and puerperium women (n=1126) from respondents in the Comprehensive Survey of People’s Living Conditions (CSPLC) conducted in 2007 by Ministry of Health, Labour and Welfare in Japan. Multiple logistic analyses showed the significant associations between mental health and psychosocial stressors: “family relationship,” “pregnancy and birth,” and “incomes/ family budgets/ debts”, regardless of “employed” or “unemployed”. After stratified by working status, whereas “one’s job” stressor had an association with mental health only for employed females, stressors for “one’s disease/long -term care” and “housework” had associations only for unemployed ones. For employed women, the primary factor for mental health was “family relationship” stressor. Although mental health status measured by K6 was not different between employed or unemployed female population, primary stressors related mental health was revealed to differ with working status. Especially, “family relationship” stressor was the highest risk factor of mental health in employed women. More importantly, the results provided evidence on the differences in associations between mental health and specific psychosocial stressors by working status. Psychosocial risk assessments and interventions on working status among pregnant and puerperium women should be imperative to pay attention for social politics.DOI: http://dx.doi.org/10.11591/ijphs.v1i2.808